A 70% Reduction in Mosquito Populations Does Not Require Removal of 70% of Mosquitoes. Issue 5 (17th April 2020) - Lega, J; Brown, H E; Barrera, R
Abstract: We added a vector control component to our existing abundance model to simulate intensive vector control in Puerto Rico. Removing 20–30% of gravid females in the model matches observed 60–80% reductions. The model's capacity to reproduce vector control increases its utility for planning and evaluation strategies.